Eliminating gender disparities in firm performance in India: Can globalization bridge the gap? - Shruti Shastri (Asian Development Bank Institute (ADBI), 2024)
A growing literature is investigating the nature and size of the disparities in the performance of firms led by men and women. The extant literature in this regard is inconclusive and provides support for both the women's under-performance hypothesis and the superior performance of women-led firms. A noticeable feature of the available literature is the heterogeneity of results across regions, which provides the rationale for country-specific studies. The purpose of this study is to establish whether there is a performance gap between women- and men-led firms in the Indian context and to what extent globalization contributes to this gap. Using data from the World Bank Enterprise Survey of 9376 firms, the present study finds that firms with a female top manager exhibit higher mean labor productivity and a higher level of internationalization than firms with a male top manager. For a pooled sample of men- and women-led firms, the study finds a positive impact of export intensity, global value chain (GVC) participation, and foreign ownership on firm performance. The positive impact of export intensity and GVC participation is, however, larger for firms with female managers. The findings further reveal that having a female top manager positively moderates the relationship between exports and firm performance and GVC and firm performance. In other words, women-managed businesses are able to harness greater productivity gains from exporting and GVC participation than men-managed businesses. The Oaxaca-Blinder decomposition analysis of the labor productivity gap between women- and men-managed firms also shows that not only the levels of export intensity and GVC participation but also the returns from such participation contribute to the higher productivity of women-led firms over men-led firms.
Keywords: F2; F6; L2; 330; gender disparities; firm performance; women-managed firms; globalization